Microbiological Quality of Broiler Chicken Carcasses Processed in Serdang Wet Markets - Bhusal, Parsu Ram (2004)
Foodborne diseases associated with the consumption of poultry meat and its processed products are of public health significance worldwide. In Malaysia, modern large scale processing plants exist together with several small scale poultry slaughter units in wet markets with minimum technological interventions. Previous studies revealed a high prevalence of indicator organisms and pathogens in chicken carcasses freshly slaughtered and those in the retail markets. Thus, this study was undertaken to determine the microbiological quality of poultry carcasses processed in wet markets and evaluate the reduction of microbial contamination using chlorinated water and iced water. Three wet market poultry slaughter stalls (Stall A, B and C) at Taman Sri Serdang about one kilometer from University Putra Malaysia (UPM) were studied. A total of 1051 swab samples (cloacal swabs taken from cloaca and 4 carcass swabs taken from breast and thigh skin surfaces of the broiler chicken) were collected from five different sampling sites, i.e:(a) prior to slaughter (b) prior to scalding (c) post-defeathering (d) post-evisceration and (e) post-rinsing in three different visits in each stall. The Standard Plate count (SPC), Coliform Plate count (CPC) and Escherichia coli count (E. coli count) and the prevalence of Salmonella, Campylobacter and vancomycin resistant enterococcus (VRE) were determined by standard bacteriological methods. The overall SPC, CPC and E. coli counts were found to be high at all the stages in all three stalls. The counts decreased at post-defeathering, but increased again at post-evisceration and decreased at post-rinsing. The CPC and E. coli counts were significantly higher (P≤0.05) in stall C compared to stall A and B. The highest count in stall C could be due to the differences in processing practice such as bleeding of carcasses in a tank filled with water, use of contaminated water from evisceration tank to clean the feathers attached in defeathering machine and evisceration of carcasses in a tank filled with contaminated water. At post-rinsing, the SPC, CPC and E. coli counts were up to 18 (log1.25), 2,800 (log3.46) and 27,000 (log 4.43) times higher respectively than that of Malaysian microbiological guidelines and the microbiological guidelines recommended for meat and poultry by international agencies. Similar trends were observed on the prevalence of pathogens studied. A high prevalence of Salmonella (57%), VRE (40%) and Campylobacter (7%) in the 5 post-rinsing carcasses compared to other processing sites revealed that faecal contamination and cross-contamination of the pathogens had occurred during processing. The use of chlorinated water and iced water was found to have significantly reduced (P≤0.05) the microbiological count in the carcasses. The SPC, CPC and E. coli counts were reduced up to 224 (log 2.35), 37(log1.57) and 26 (log1.41) times in chlorinated water and 32 (log1.51), 14 (log1.15) and 8 (log 0.90) times in iced water, respectively. The high prevalence of pathogens and indicator organisms in the carcasses revealed that chickens in wet markets were processed in poor hygienic environment. A more serious attention should be given by the concerned authorities and agencies to upgrade processing procedures ensuring supply of wholesome poultry meat for consumer’s protection. The use of chlorinated and iced water to decontaminate the poultry carcasses should be enforced in all wet market poultry processing stalls in the country.